The Interplay of Cinematic Techniques and Narrative Elements in Constructing Irony in Jordan Peele’s Get Out (2017) - Arila Nur Rochman; Yuyun Nurulaen; Lili Awaludin (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze how irony is constructed in the film Get Out (2017) through the interplay between narrative elements and cinematic techniques. This study employs a qualitative method with a textual analysis approach to six scenes selected purposively based on the types of irony represented, such as situational irony, dramatic irony, and verbal irony. Data were collected through documentary analysis by repeatedly watching in the film, identifying scenes containing irony, and noting relevant dialogue and visual aspects. The results indicate that irony in the film emerges not only through the plot and dialogue but is also reinforced by cinematic techniques such as lighting, camera angles, and framing. These elements play a role in shaping the audience’s perception of the difference between the surface meaning and the hidden meaning. Thus, the interaction between narrative and cinematic elements produces a strong ironic effect while conveying social criticism of covert racist practices.